Optimization and Characterization of Extruded Partially Pregelatinized Cassava Starch as Filler-Binder - T N Saifullah Sulaiman; Gabriela Kasih Mawarni; Rumiyati Rumiyati (Indonesian Journal of Pharmacy, 2023)
In order to use starch as a filler-binder, the pregelatinization method by extrusion can enhance the flow characteristics and compressibility of starch. This study aimed to find the optimum process parameter for producing partially pregelatinized cassava starch (PPCS) using twin screw extrusion and characterizing it as a filler-binder excipient. For arranging experimental trials, a three-level Box-Behnken design with three independent variables—starch moisture content (ranged from 20% to 40%), extrusion temperature (ranged from 50°C to 70°C), and screw speed (ranged from 10 rpm to 30 rpm)—was used to make PPCS. The response surface methodology approach was used for optimization. The desired filler-binder characteristic of PPCS was defined as having good flowability and compactibility properties. The most desirable process parameter was achieved by combining 39.9 percent starch moisture content, 70°C extrusion temperature, and 25.8 rpm screw speed. The results showed that optimized PPCS has good flow properties and also good water absorption capacity. The optimized PPCS had a polygonal shape and a size range of 149-400μm. PPCS showed birefringence characteristics under polarized light, indicating a large number of undamaged starch granules. The PPCS XRD pattern showed peaks at 15°, 17°, 18°, and 23°, and also a relative crystallinity of 27.3 percent. When analyzed with DSC, PPCS revealed glass transition curves and a gelatinization degree of 36.01 percent.